THE DEVIATIONS OF MORPHOSYNTAX OF GRAMMATICAL CATEGORIES IN THE ESSAYS OF THE ENGLISH GRADUATE STUDENTS OF STATE UNIVERSITY OF PADANG - Roza, Veni (English Department FBS UNP, 2009)
This research dealt with deviations or errors of morphosyntax of grammatical categories which consist of structural properties and distributional properties of nouns, verbs, adjectives and adverbs made by the first semester English graduate students of State University of Padang (UNP) in writing their essays. It aimed at explaining what errors of morphosyntax of grammatical categories committed by those students in writing their essays. The subjects of this research were the first semester English graduate students of 2008/ 2009 academic year of UNP. There were 15 randomly selected students who took the course of Academic Writing as the subjects of the research. The instrument used was through a test with one administration where the lecturer asked the students to construct essays based on the topics given. The analysis of data was based on theories proposed by Payne (1997) describing morphosyntax, error analysis method by James (1998) and Scovel (2001). It was found out that deviations of morphosyntax of grammatical categories mostly occurred. First, in the mis-formation of verbs (54.45%) as a structural property that exhibits subject agreement and in the omission of verbs which serves as predicates of clauses as a distributional property. Second, in the misformation of nouns (32.07%) exhibiting number as structural property and in the omission of nouns as a distributional property which serves as heads of noun phrases. Third, in the misformation of adjective (8.33%) which exhibits predicative function; and fourth in the errors of omission suffix –ly in adverbs (5.05%) modifying verbs. The findings reveal that the use of correct morphosyntax of grammatical categories of the first semester English graduate students of 2008/ 2009 academic year of UNP in writing essays is low implication?